Remote ischemic preconditioning does not increase circulating or effector organ concentrations of proopiomelanocortin derivates. (October 2015) - Birkelund, Thomas; Obad, Damir Salskov; Matejec, Reginald; Bøtker, Hans Erik; Ravn, Hanne Berg
Abstract Objectives. The aim of the present study was to compare changes in circulating levels of proopiomelanocortin (POMC) derivates and lactate after remote ischemic preconditioning (IPC) and physical exercise. Introduction. Remote IPC (rIPC) is cardioprotective following acute myocardial infarction and major cardiac surgery. A blood-borne, transferable factor, released following not only rIPC but also vigorous exercise, mediates protection that is abolished by naloxone suggesting involvement of an opioid-receptor-dependent pathway. Design. Eight healthy volunteers underwent rIPC by four cycles of 5-min inflation of a pneumatic tourniquet to 200 mmHg interrupted by 5 min of deflation. Subsequently, circulating plasma levels of POMC derivates, cortisol, and lactate were measured. After 3 days, the volunteers completed a vigorous exercise program, after which the same compounds were measured. Results. While rIPC was not associated with any significant increase in circulating POMC derivates or lactate, exercise induced significant elevation of both compared with baseline. Conclusions. We were not able to demonstrate a detectable increase in circulating POMC derivates by a standard rIPC stimulus, suggesting that rIPC effect is not mediated by local or detectable central release of these derivates.